Carcass and cut traits in nulliparous and lambed female sheep of different ages and genetic groups - Geisa Isilda Ferreira Esteves; Vanessa Peripolli; Candice Bergmann Tanure; Jurandir Rodrigues de Souza; Helder Louvandini; Concepta McManus (Acta Scientiarum. Animal Sciences, 2018)
Two experiments were carried out to evaluate the influence of genetic group, pregnancy and animal age on the carcass traits and commercial cut patterns of sheep carcasses. In the first experiment, the effect of pregnancy and genetic group were evaluated on 61 eleven month old Santa Inês ewes and their crosses with Texel, Dorper and Ile de France. Experiment 2 was carried out with 132 Santa Inês nulliparous or lambed ewes slaughtered with ages ranging from 6 to 48 months to evaluate the influence of age on carcass traits. For both experiments, hot carcass weight, cold carcass weight, carcass yield, cold carcass yield and carcass length were measured, as well as the yields and percentages of shoulder, neck, loin, belly, ribs, leg and leg length and perimeter. In experiment 1, the Santa Inês breed presented similar carcass and cut traits compared to the others genetic groups evaluated, except for fasting body weight. Lambed animals had lower body condition score than nulliparous females. In experiment 2, fasting body weight, loin, rib and leg weights, as well as the leg perimeter, presented a quadratic effect with increasing age. Ideal slaughter age is before 16 months to obtain more expensive cuts.